2023
DOI: 10.1371/journal.pone.0280847
|View full text |Cite
|
Sign up to set email alerts
|

Integrated network pharmacology and molecular modeling approach for the discovery of novel potential MAPK3 inhibitors from whole green jackfruit flour targeting obesity-linked diabetes mellitus

Abstract: The current study investigates the effectiveness of phytocompounds from the whole green jackfruit flour methanol extract (JME) against obesity-linked diabetes mellitus using integrated network pharmacology and molecular modeling approach. Through network pharmacology, druglikeness and pharmacokinetics, molecular docking simulations, GO analysis, molecular dynamics simulations, and binding free energy analyses, it aims to look into the mechanism of the JME phytocompounds in the amelioration of obesity-linked di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The free binding energy of interaction was −5.3 kcal/mol. It is reported that vicenin-2, purvalonol and rutin also interacted with VAL56, LEU173, ALA69, CYS183, ILE48 residues of MAPK3 by forming hydrophobic interactions [ 60 ]. Numerous hydrophobic residues surrounding the ligands within the binding pocket suggest that hydrophobic interactions play a role in stabilizing the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The free binding energy of interaction was −5.3 kcal/mol. It is reported that vicenin-2, purvalonol and rutin also interacted with VAL56, LEU173, ALA69, CYS183, ILE48 residues of MAPK3 by forming hydrophobic interactions [ 60 ]. Numerous hydrophobic residues surrounding the ligands within the binding pocket suggest that hydrophobic interactions play a role in stabilizing the complex.…”
Section: Resultsmentioning
confidence: 99%
“… Rao et al (2021) demonstrated that consumption of jackfruit flour can be selected as a medical nutritional therapy in place of equivalent amounts of rice or wheat flour of daily meal in patients with T2DM. Besides, jackfruit extracts has also been proved possess the ability for the management of diabetes mellitus ( Ajiboye et al, 2018 , Maradesha et al, 2023 ).Regulation of carbohydrate and fat digestion and/or absorption in the gastrointestinal tract may be another promising strategy for the prevention of T2DM. Recent studies have shown that the consumption of fermentation food is linked to reducing the risks of obesity, and the inhibition of digestive enzyme activities has been regarded as one of the most crucial action mechanisms underlying the beneficial effects ( Yoon et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further network pharmacology was employed to thoroughly investigate the mechanism of action of pharmaceuticals, facilitating the advancement of novel drugs through a multi-target, multi-component strategy. ( Maradesha et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%